Why are there discrepancies between depressed patients’ Global Rating of Change and scores on the Patient Health Questionnaire depression module? A qualitative study of primary care in England - Alice Malpass; Glyn Lewis; Jude Robinson; Christopher Dowrick; Naila Khan; Louise Fusco (BMJ Open)
Objectives Our aims were to investigate discrepancies between depressed patients’ GlobalRating of Change (GRC) and scores on the Patient Health Questionnaire depression module (PHQ-9). Our objectives were to ascertain patients’ views on the source and meaning of mismatches and assess their clinical significance.Design Qualitative study nested within a cohort, in a programme investigating the indications for prescribing antidepressants that will lead to a clinical benefit.Setting Primary care practices in north-west England.Participants We invited 32 adults with a recent diagnosis of depression and evidence of mismatch between GRC and PHQ-9 Scores to participate. Of these, 29 completed our interviews; most were women, identified as white British, had high school education or higher, were employed or retired and had been depressed for a long time.Main measures We conducted semistructured interviews with a topic guide, focusing on experiences of depression; treatment experiences and expectations; effectiveness of the questionnaires; reasons for the mismatch; and social factors. Interviews were transcribed and subjected to interpretative phenomenological analysis.Results We identified four themes as explanations for mismatch between GRC and PHQ-9: perceptions that GRC provided a more accurate assessment of current mental state than PHQ-9; impact of recent negative or positive life events on either measure; personal understanding of depression as normally fluctuating, and tendency to underscore on PHQ-9 as a means of self-motivation; and lack of recall.Conclusions The combined used of the PHQ-9 and a more open question better captures the patient’s unique experiences of mental health. This approach ascertains the relevance of symptoms to the individual’s experience and influences treatment decisions.Study registration This study was an element of NIHR Programme Grant RP-PG 0610 10048.